2022
DOI: 10.1039/d2sc05479e
|View full text |Cite
|
Sign up to set email alerts
|

Fe2(MoO4)3 assembled by cross-stacking of porous nanosheets enables a high-performance aluminum-ion battery

Abstract: Rechargeable aluminum-ion batteries have attracted increasing attention owing to the advantageous multivalent ion storage mechanism thus high theoretical capacity as well as inherent safety and low cost of using aluminum....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Liang et al reported a metal oxide, Fe 2 (MoO 4 ) 3 , with excellent stability which was assembled by cross-stacking porous nanosheets. 9 Liu et al proposed and demonstrated the Al-storage mechanism of an alloying reaction with a bimetallic activation center. 10 Li et al tuned the gradients of heteroatoms, N and P, doped in the MOF-derived porous carbon in a C@N–C@N,P–C heterostructure.…”
mentioning
confidence: 99%
“…Liang et al reported a metal oxide, Fe 2 (MoO 4 ) 3 , with excellent stability which was assembled by cross-stacking porous nanosheets. 9 Liu et al proposed and demonstrated the Al-storage mechanism of an alloying reaction with a bimetallic activation center. 10 Li et al tuned the gradients of heteroatoms, N and P, doped in the MOF-derived porous carbon in a C@N–C@N,P–C heterostructure.…”
mentioning
confidence: 99%